Potency of Piper crocatum Decoction as an Antihiperglycemia in Rat Strain Sprague dawley - MEGA SAFITHRI; FARAH FAHMA (HAYATI Journal of Biosciences, 2008)
Current researches for appropriate hypoglycemic agents focused on plants for traditional medicine. Traditionally in diabetic treatment, people used decoctions of Piper crocatum (Piperaceae). However, there is no phytochemical data of decoctions extract of P. crocatum. Hence, the aims of this study were to explore the phytochemical of P. crocatum decoctions and its antihyperglicemic activity. Fresh leaves of P. crocatum were boiled in water to obtain decoction and were examined phytochemical compounds by using Harbone assay. Antihyperglicemic activity of P. crocatum decoction extract was orally fed to alloxan induced diabetic rats. Results showed that P. crocatum decoction extract contained flavonoids, tanins, and alkaloids. Ten days of daily treatment of various doses decoction extract of P. crocatum led to reduce blood sugar level by 10-38% and prevent fall in body weight level by 5-52%. This result showed the same activity as Daonil treatment, which was the diabetic drug. Hence, this extract showed antihyperglicemic activity in alloxan-induced diabetic rats and increasing of their body weight. Key words: Piper crocatum, antihyperglicemic, phytochemical